UTILIZATION OF SHRIMP HEAD AND FISH BONE MEAL FROM FISHERIES WASTE AS LOCAL FISH FEED INGREDIENTS IN LINGGA - Agriandini, Maulina; Purnamasari, Tina; Kartika, Nurmayuni; Tartila, Shobrina Silmi Qori; Oktary, Rini; Pratiwi, Lastri; Rahayu, Sri Panca (Aurelia Journal, 2024)
The problem faced by fish farmers in Lingga is that the feed is quite expensive and rarely found on the local market. The existence of shrimp heads and fish bones are often found in Dabo as waste from processed shrimp crackers and fish balls that have not been utilized. The research aimed to evaluate the quality of fish feed from local fish meal, shrimp head meal and fish bone meal based on organoleptic, physical, and chemical tests. The treatments tested in this study consist of three threatments, namely: feed A (48%), feed B (35%), and feed C (comercial feed). The organoleptic showed that feed have a fibrous texture, typical coconut aroma, and brown color. The results of water stability showed that feed A (86,50 minutes±1,63), B (87,00 minutes±1,29), C (91,75  minutes±0,96) and dispersion of solids feed A (9,38% ±0,95), B (9,50%±0,71), C (8,63%±0,85). The sinking velocity showed that feed A (3,79 cm/s±0,23), B (3,32 cm/s±0,24), C (4,61 cm/s±0,18). The hardness level of feed A (91,63%±1,38), B (91,38%±2,66), C (94,63%±2,14). The proximate of feed has a moisture of 7,53% (A); 5,28% (B); 6,69% (C), ash of 19,95% (A); 17,85% (B); 12,03% (C), crude protein of 49,07% (A); 36,14% (B); 31,23% (C), crude lipid of 4,28% (A); 4,90% (B); 11,63% (C), and carbohydrate 19,19% (A); 35,84% (B); 38,43% (C). The results of  physical and proximate  indicated that ingredients local feedstuff have the potential as fish feed except moisture and ash.